Il lettore 'distratto' Leggere e comprendere nell'epoca degli schermi digitali - Nardi, Andrea (Studi e saggi, 2022)
In the current media landscape, digital devices seem to undermine traditional learning and reading practices. Overwhelmed by cognitive overload and a flood of information stimuli, constantly busy scrolling through touch screens, today's readers often show a "distracted", hasty and "impatient" approach; they skim-read through text without in-depth comprehension, thus risking to miss out on the full understanding of meanings. Following the increased diffusion of digital reading, both inside and outside of schools, researchers are called upon to evaluate its strengths and weaknesses, prerogatives and risks. Do the new reading modalities restructure our cognitive habits and our thinking? Is it better to read on paper or through digital texts? Does online reading require new competencies and skills? How can we teach students to read "critically" on the screen? These are just some of the questions which this volume will try to answer, benefiting from the contribution of various branches of knowledge ranging from pedagogy to media studies, from cognitive psychology to neuroscience; standing in between the two opposing views of the "myth of superficiality" and the "myth of depth", and avoiding both uncritical optimism regarding the present and nostalgic idealization of a past forever lost.